Method of hygienic assessment of soil : methodical recommendations to prepare 3rd year students for practical classes for the discipline of «Hygiene and ecology» [Electronic resource] - Redka, Iryna Vasilyivna; Редька, Ірина Василівна (Kharkiv : V.N. Karazin Kharkiv National University, 2023)
Methodological recommendations include the main physical and chemical properties of soils and methods of their assessment. The rules of soil sampling for further laboratory research, depending on its purpose, are disclosed. Schemes for determining helminthological, entomological and bacteriological indicators of sanitary conditions and soil contamination are given. Legislatively approved regulations and standards regarding acceptable levels of soil pollution are given. Methodical recommendations contain theoretical material, test questions for self-control, situational problems, a list of modern recommended literature.

У методичних рекомендаціях наведено основні фізичні та хімічні властивості ґрунтів та методики їх оцінки. Розкрито правила відбору проб ґрунтів для подальшого лабораторного дослідження в залежності від його мети. Наведено схеми визначення гельмінтологічних, ентомологічних та бактеріологічних показників санітарного стану та забруднення ґрунту. Наведено законодавчо затверджені нормативи та стандарти щодо прийнятних рівнів забруднень ґрунтів. Методичні рекомендації містять теоретичний матеріал, тестові питання для самоконтролю, ситуаційні задачі, список сучасної рекомендованої літератури.
Методика гігієнічної оцінки грунту : методичні рекомендації до підготовки студентів 3 курсу до практичних занять з дисципліни «Гігієна та екологія» [Електронний ресурс].
Methodical recommendations
Keywords: MEDICINE; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; texture; porosity; air and water permeability; humidity; capillarity; color; soil acidity; Khlebnikov's sanitary index; chemical and epidemic safety of the soil; текстура; пористість; повітре- та водопроникність; вологість; капілярність; колір; кислотність ґрунту; санітарний показник Хлебнікова; хімічна та епідемічна безпечність ґрунту